Anglo-Free French strategy in Northwest Africa: operation against Dakar, september 1940. - Brahim HAROUNI (Revue des Sciences Humaines, 2000)
After the fall of France in 1940, the British Prime Minister, Winston Churchill, tried hard to persuade Marshall Petain to continue the war from North Africa but his effort was of no avail. This is the reason why Winston Churchill accepted to mount a combined operation with the Free-French under the leadership of General de Gaulle to seize the French naval base of Dakar.